Determinação de elementos terras raras por espectrometria de absorção atômica de alta resolução com fonte contínua por chama - Wiethan, Bruna Avila (2018)
In the present work, two methods of determination of rare earth elements by high resolution continuum source flame AAS was developed, being a sequential and a simultaneous method. The sequential method allowed the determination of an erbium, scandium, europium, holmium, ytterbium, yttrium, neodymium, samarium, terbium and thulium in natural water samples as having no pre-treatment. Limits of detection were between 0.003 μg mL-1 and 0.473 μg mL-1 for the most sensitive (Yb) and less sensitive (Tb) measurements, respectively. Accuracy was assessed through comparative analysis by inductively coupled plasma mass spectrometry. The method for simultaneous determination of Ca and Gd presented, respectively, detection limits equal to 9 μg mL -1 and 1,824 μg mL -1. This was developed for the application in magnetic resonance contrast samples based on gadolinium chelates as a tool in the determination of impurities / contaminants present in such samples. Less sensitive absorption lines of dysprosium and holmium could also be identified in the same spectral window, allowing the visualization of the signal corresponding to these four elements simultaneously.